The Relationship Between Fruit and Vegetable Consumption Habits, Emotional Eating, and Sedentary Lifestyle with the Nutritional Status of Adolescents - Hidayatusy Syukrina Puteri; Lamtiur Elita Sari; Ai Kustiani (CV. CENDIKIA JENIUS INDONESIA, 2025)
The nutritional status of adolescents in Indonesia remains a serious concern, as indicated by the high prevalence of malnutrition caused by inadequate balanced nutrition intake, emotional eating behavior, and sedentary lifestyle. This study aimed to determine the relationship between sedentary lifestyle, emotional eating, and fruit and vegetable consumption habits with the nutritional status of adolescents at SMA N 1 Banding Agung, Ogan Komering Ulu Selatan. This study employed a quantitative design with a cross-sectional approach. A total of 86 respondents were selected using purposive sampling. The study was conducted from May to June 2025. Data analysis was performed using the Chi-square test as the data were normally distributed. Data were collected using validated FFQ, DEBQ, and ASAQ questionnaires. The results showed significant associations between vegetable consumption habits (p=0.003), fruit consumption (p=0.001), emotional eating (p=0.033), and sedentary lifestyle (p=0.002) with adolescents’ nutritional status. Most respondents with inadequate fruit and vegetable intake, high emotional eating, and high sedentary lifestyle exhibited poor nutritional status. Adolescents with sufficient fruit and vegetable consumption tended to have better nutritional status. In conclusion, adolescents’ nutritional status is influenced by dietary behavior, emotional regulation, and physical activity levels. It is recommended that adolescents increase their intake of fruits and vegetables according to balanced nutrition guidelines, reduce emotional eating behavior, and engage in more physical activity to maintain optimal nutritional health.